Concerns about falling in people with Mild Cognitive Impairment and dementia: a scoping review of exercise interventions - Dove, Erica; Hewston, Patricia; Wang, Rosalie H.; Patterson, Kara K.; Astell, Arlene J. (Frontiers in Dementia, 2024)
Background: Concerns about falling (e.g., low balance confidence) increase fall risk in older populations with balance impairments. Exercise can improve physical limitations associated with falls (e.g., poor balance), which are more prevalent in people with Mild Cognitive Impairment (MCI) and dementia. This scoping review aimed to understand exercise interventions targeting concerns about falling in people with MCI and dementia. Methods: Using Arksey and O'Malley's five-stage scoping review framework, 968 search combinations were run across six electronic databases from inception to September 15, 2023. Articles were available in English full text, featured original peer-reviewed research with an intervention study design, targeted people with MCI or dementia with the exercise intervention, and included concerns about falling as an outcome measure. Results: Of the 2,111 articles screened, 27 met the inclusion criteria. Only one article looked at concerns about falling as a primary outcome; in the remaining studies, concerns about falling were a secondary outcome. Multi-modal interventions (i.e., containing more than one type of exercise) were most common, with balance and strength as the most frequently employed exercise types. Secondary results are presented on (i) intervention details, (ii) outcomes and measures for concerns about falling, (iii) participant accommodations, and (iv) components of effective interventions for concerns about falling. Conclusions: There is a lack of focus on concerns about falling experienced by people with MCI and dementia. Although concerns about falling were not the primary outcome of most papers, the results highlight the potential of exercise interventions to help address concerns about falling and other fall risk factors (e.g., balance, cognition) in people with MCI and dementia.